2015
DOI: 10.1002/jat.3220
|View full text |Cite
|
Sign up to set email alerts
|

Zerovalent Fe, Co and Ni nanoparticle toxicity evaluated on SKOV‐3 and U87 cell lines

Abstract: We have considered nanoparticles (NPs) of Fe, Co and Ni, three transition metals sharing similar chemical properties. NP dissolution, conducted by radioactive tracer method and inductively coupled plasma mass spectrometry, indicated that NiNPs and FeNPs released in the medium a much smaller amount of ions than that released by Co NPs. The two considered methodological approaches, however, gave comparable but not identical results. All NPs are readily internalized by the cells, but their quantity inside the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 58 publications
(69 reference statements)
0
28
0
Order By: Relevance
“…However, considering the increased usage of nanoscale materials, the possible effects of these materials on the health of organisms and the environment are inevitable. In recent years, environmental toxicological studies have employed a slight quantitative approach to qualitative assessments (Gornati et al 2016). Nowadays, nanoparticle pollution is a new and dangerous problem (Shi and Wang 2004;Doyle et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…However, considering the increased usage of nanoscale materials, the possible effects of these materials on the health of organisms and the environment are inevitable. In recent years, environmental toxicological studies have employed a slight quantitative approach to qualitative assessments (Gornati et al 2016). Nowadays, nanoparticle pollution is a new and dangerous problem (Shi and Wang 2004;Doyle et al 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Based on our previous experience and published data [3,21], we selected HSP70, MT2A, MLL, SDHB1, CASP3, QSEC1, and VMP1 as target genes to determine gene expression. Values, derived from five subjects, were normalized with three reference genes, GAPDH, β2m and RPL13 according to the method of Palombella et al [19] and quantified by using the 2 -Ct method.…”
Section: Rna Extraction and Qpcrmentioning
confidence: 99%
“…Furthermore, another aspect that should be taken into account when studying NPs is so-called 'dissolution', a phenomenon that can occur when NPs are placed in an aqueous solvent such as culture medium or saline solution. In previous studies, we demonstrated that Co-NPs can gradually dissolve in the culture medium, generating ions whose presence may contribute to NP toxicity [3,9,15].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the various applications described above, iron-based NPs raise concerns for the potential risk of exposure through ingestion, which can occurs both into the aquatic environment, this being the ultimate recipient of NPs that are intentionally or accidentally spilled into it, and when they are used as nanoingredients. In vitro (Gornati et al 2016;Coccini et al 2019) and in vivo experiments on mammals (Cappellini et al 2015;Feng et al 2018) have been performed to evaluate iron NP toxicity. Moreover, several iron NPs (i.e.…”
Section: Introductionmentioning
confidence: 99%